Context‐dependent conservation of the cavity‐nesting European Roller. (10th August 2018) - Finch, Tom; Branston, Claire; Clewlow, Harriet; Dunning, Jamie; Franco, Aldina M. A.; Račinskis, Edmunds; Schwartz, Timothée; Butler, Simon J.
Abstract : To maximize the effectiveness of conservation interventions, it is crucial to have an understanding of how intraspecific variation determines the relative importance of potential limiting factors. For bird populations, limiting factors include nest‐site availability and foraging resources, with the former often addressed through the provision of artificial nestboxes. However, the effectiveness of artificial nestboxes depends on the relative importance of nest‐site vs. foraging resource limitations. Here, we investigate factors driving variation in breeding density, nestbox occupation and productivity in two contrasting study populations of the European Roller Coracias garrulus, an obligate cavity‐nesting insectivorous bird. Breeding density was more than four times higher at the French study site than at the Latvian site, and there was a positive correlation between breeding density (at the 1‐km 2 scale) and nest‐site availability in France, whereas there was a positive correlation between breeding density and foraging resource availability in Latvia. Similarly, the probability of a nestbox being occupied increased with predicted foraging resource availability in Latvia but not in France. We detected no positive effect of foraging resource availability on productivity at either site, with most variation in breeding success driven by temporal effects: a seasonal decline in France and strong interannual fluctuations in Latvia. Our results indicate that the factors limiting local breeding density can vary across a species' range, resulting in different conservation priorities. Nestbox provisioning is a sufficient short‐term conservation solution at our French study site, where foraging resources are typically abundant, but in Latvia the restoration of foraging habitat may be more important.